Use of drug-eluting stents in the treatment of coronary artery disease - Aripov Marat Asanovich; Rakhimov Ravil Nailevich (Theoretical Hypotheses and Empirical Results, 2025)
Constant improvement of PCI techniques and modernization of instruments in interventional cardiology today make it possible to effectively and safely perform endovascular treatment of patients with complex lesions, including extended forms of coronary artery lesions. In recent years, drug-eluting stents (DES) with ultra-thin struts (65 microns), 40-60 mm long, including variable diameter stents (VDS), have appeared on the endovascular treatment instrumentation market.